Hand-washing at critical times and associated factors among mothers of children under-five in Ethiopia: a systematic review and meta-analysis - Gizaw Sisay; Negasa Eshete; Kassa Genetu (Italian Journal of Pediatrics)
Abstract Good hand-washing practice is the most important preventive measure to reduce the spread of communicable disease to under-five children. Prior studies on good handwashing practice at critical times among mothers of children under-five age in Ethiopia were extremely varied. Therefore, this meta-analysis aimed to assess the overall proportion of good handwashing practice at critical times and identify the associated factors in Ethiopia. A comprehensive search of relevant studies was performed using distinct databases. Data were extracted using Microsoft Excel spreadsheet, and exported to Stata-MPv-17 for analysis. A random-effect model was used to estimate the overall proportion of good hand-washing practice at critical times. A random or fixed effects model was used to compute the pooled AORs with their 95% Cis, which were presented on a forest plot. $${I}^{2}$$ I 2 test statistics was used for assessing heterogeneity among the included studies. The funnel plot and Egger's test were used to assess the publication bias. Ten studies were included in this systematic review and meta-analysis. The overall pooled proportion of good hand-washing practice at critical times among mothers of children under-five age in Ethiopia was 43.18% (95% CI = 31.05, 55.31). Insufficient water (AOR = 0.33, 95% CI: 0.13, 0.52), good knowledge (AOR = 1.35, 95% CI = 1.09, 1.61), desirable attitude (AOR = 4.34, 95% CI = 1.84, 6.84) and higher educational level (AOR = 0.17, 95% CI = 0.08, 0.25) were significantly associated with good practice of hand-washing at critical times. The national level of good practice of hand-washing at critical times was low. Hence, to promote good practice of hand-washing, it is essential to increase the accessibility of water and provide hygiene health education and training programs to improve knowledge and desirable attitudes of mothers.